Ang batang natutong magtipid (The child who is thrifty) - Villanueva, Rene O. (Lampara books, 2007)
"Mira is given school things by her aunt. But she sells her comb and hairband so she can buy a basket of grapes. She also sells the cloth meant foe her dress so she can have a fan. She does the same to her other school things so she can buy a bouquet of flowers. When school finally opens, nothing is left of her things, preventing her from going to school. Grandfather Uban tells the story of how a little girl who learns the value of thrift and prudence succeeds in going to school."